A low voltage activated Ca2+ current found in a subset of human ventricular myocytes. Issue 1 (1st January 2020) - Zhang, Xin; Li, Yijia; Zhang, Xiaoying; Piacentino, Valentino; Harris, David M.; Berretta, Remus; Margulies, Kenneth B.; Houser, Steven R.; Chen, Xiongwen
ABSTRACT: Low voltage activated (ICa-LVA ) calcium currents including Cav1.3 and T-type calcium current (ICa-T ) have not been reported in adult human left ventricular myocytes (HLVMs). We tried to examine their existence and possible correlation with etiology and patient characteristics in a big number of human LVMs isolated from explanted terminally failing (F) hearts, failing hearts with left ventricular assist device (F-LVAD) and nonfailing (NF) human hearts. LVA (ICa-LVA ) was determined by subtracting L-type Ca 2+ current (ICa-L ) recorded with the holding potential of −50 mV from total Ca 2+ current recorded with the holding potential of −90 mV or −70 mV. ICa- LVA was further tested with its sensitivity to 100 µM CdCl2 and tetrodotoxin. Three HLVMs (3 of 137 FHLVMs) from 2 (N = 30 hearts) failing human hearts, of which one was idiopathic and the other was due to primary pulmonary hypertension, were found with ICa-LVA . ICa-LVA in one FHLVM was not sensitive to 100 µM CdCl2 while ICa-LVA in another two FHLVMs was not sensitive to tetrodotoxin. It peaked at the voltage of −40~-20 mV and had a time-dependent decay faster than ICa-L but slower than sodium current (INa ). ICa-LVA was not found in any HLVMs from NF (75 HLVMs from 17 hearts) or F-LVAD hearts (82 HLVMs from 18 hearts) but a statistically significant correlation could not be established. In conclusion, ICa-LVA was detected in some HLVMs of a small portion of human hearts that happened to be nonischemic failing hearts.